Reducing the Primary Cesarean Birth Rate: A Quality Improvement Project. (13th July 2017) - Javernick, Julie A.; Dempsey, Amy
Abstract : Introduction: Research continues to support vaginal birth as the safest mode of childbirth, but despite this, cesarean birth has become the most common surgical procedure performed on women. The rate has increased 500% since the 1970s without a corresponding improvement in maternal or neonatal outcomes. A Colorado community hospital recognized that its primary cesarean birth rate was higher than national and state benchmark levels. To reduce this rate, the hospital collaborated with its largest maternity care provider group to implement a select number of physiologic birth practices and measure improvement in outcomes. Process: Using a pre‐ and postprocess measure study design, the quality improvement project team identified and implemented 3 physiologic birth parameters over a 12‐month period that have been shown to promote vaginal birth. These included reducing elective induction of labor in women less than 41 weeks' gestation; standardizing triage to admit women at greater than or equal to 4 cm dilation; and increasing the use of intermittent auscultation as opposed to continuous fetal monitoring for fetal surveillance. The team also calculated each obstetrician‐gynecologist's primary cesarean birth rate monthly and delivered these rates to the providers. Outcomes: Outcomes showed that the provider group decreased its primary cesarean birth rate from 28.9% to 12.2% in the 12‐month postprocess measure period. The 57.8% decrease is statistically significant (odds ratio [OR], 0.345; z = 6.52, P < .001; 95% confidence interval [CI], 0.249‐0.479). Discussion: While this quality improvement project cannot be translated to other settings, promotion of physiologic birth practices, along with audit and feedback, had a statistically significant impact on the primary cesarean birth rate for this provider group and, consequently, on the community hospital where they attend births.